Village Fund Management (Study Of Village Fund Budget Effectiveness In Pilolahunga Village) - LDjaafar, Lucyane; Mozin, Nopiana; Rahmola, Aldi (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
The purpose of this study was to determine how the effectiveness of VillageFund Management in pilolahunga village and the factors that inhibit theeffectiveness of Village Fund Management in Pilolahunga village. The methodused in this study is Qualitative, with a descriptive approach. Data collectiontechniques used in this study are by means of case studies, namely: readingbooks, literature, or legislation related to the problem, and also field studies,namely: interviews, observations, and documentation.The results of theresearch on Village Fund Management in pilolahunga village are (1) in thefield of village governance, village fund management has been realized well oreffectively. In terms of village development, the village government allocates abudget of 48% and has been realized in fiscal year 2019, but has not yet had animpact on the needs of the community. Meanwhile, in the field of empowermentand development of rural communities, apsek is only a priority for institutionaldevelopment and strengthening without regard to health, education andeconomic strengthening of rural communities. (2) factors that affect theeffectiveness of Village Fund Management in Pilolahunga village are humanresources and lack of community participation.